Isolation of Bacillus thuringiensis from the state of Amazonas, in Brazil, and screening against Aedes aegypti (Diptera, Culicidae) - Soares-da-Silvaa, Joelma; Soares Pinheiro, Valeria Cristina; Litaiff-Abreu, Eleilza; Polanczyk, Ricardo Antonio [UNESP]; Tadei, Wanderli Pedro (Soc Brasileira Entomologia, 2015)
We investigated the use of Bacillus thuringiensis isolated in the state of Amazonas, in Brazil, for the biological control of the dengue vector Aedes aegypti. From 25 soil samples collected in nine municipalities, 484 bacterial colonies were obtained, 57 (11.78%) of which were identified as B. thuringiensis. Six isolates, IBt-03, IBt-06, IBt-07, IBt-28, IBt-30, and BtAM-27 showed insecticidal activity, and only BtAM-27 presents the five genes investigated cry4Aa, cry4Ba, cry10Aa, cry11Aa, and cry11Ba. The IBt-07 and IBt-28, with lower LC50 values, showed equal toxicity compared to the standards. The isolates of B. thuringiensis from Amazonas constitute potential new means of biological control for A. aegypti, because of their larvicidal activity and the possibility that they may also contain new combinations of toxins. (C) 2015 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Amazonian; Bioinsecticide; Dengue; Vector